1998
DOI: 10.1097/00042560-199812010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With HIV-Infected Patients' Recognition and Use of HIV Medications

Abstract: In 1996, we interviewed 224 HIV-infected patients (54% men, 63% African American) receiving HIV medical care in St. Louis, Missouri about their recognition, prior use, and current use of HIV medications. Of 221 respondents who had heard of at least one antiretroviral drug, only 2 respondents reported they had never taken antiretroviral drugs. Multivariate logistic regression among respondents with CD4 counts <500 cells/mm3 identified sociodemographic variables (gender, race, education, and site of care) that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…In 1996, a study of 224 people receiving HIV medical care in St. Louis found that 98% of clients reported having heard of AZT and 83% of these reported having taken the drug. 45 Among 1,034 adults recruited from a Los Angeles-area AIDS service organization, 66% reported taking a protease inhibitor in November 1996. 46 Among injection drug users with AIDS who were enrolled in New Jersey Medicaid in 1988-1996, 74% had a prescription filled for at least one antiretroviral medication.…”
Section: Antiretroviral Usementioning
confidence: 99%
See 4 more Smart Citations
“…In 1996, a study of 224 people receiving HIV medical care in St. Louis found that 98% of clients reported having heard of AZT and 83% of these reported having taken the drug. 45 Among 1,034 adults recruited from a Los Angeles-area AIDS service organization, 66% reported taking a protease inhibitor in November 1996. 46 Among injection drug users with AIDS who were enrolled in New Jersey Medicaid in 1988-1996, 74% had a prescription filled for at least one antiretroviral medication.…”
Section: Antiretroviral Usementioning
confidence: 99%
“…(See Table 1.) Overall, 15 studies had data collection periods that included 1996 or later, [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] i.e., after FDA approval for use of the first protease inhibitor in late 1995. Ten of the these reports specifically measured the use of either protease inhibitors, NNRTIs, or HAART.…”
Section: Antiretroviral Usementioning
confidence: 99%
See 3 more Smart Citations